User’s Acceptance on e-Hailing System as Alternative Transportation by Using Modal Shift - Nazri, Muhammad Azmie; Ambak, Kamarudin; Ab Ghani, Ahmad Raqib; Mat Yazid, Muhamad Razuhanafi (International Journal of Integrated Engineering, 2021)
e-Hailing system is one of the mediums that are functioning to minimize the person on using the private transportation. Due to modern technology era, internet is used to ease the user in communication. With the internet platform assist, the e-Hailing system has well in management with the users can request the destination, travel time and also the cost for this service. The objective of this study was to identify the contributing factors effect to use e-Hailing system and also to analyze modal shift between public transport and e-Hailing system. Therefore, a study towards user’s acceptance on using e-Hailing system as alternative transport based on the modal shift method with Binary Logistic regression analysis was necessary to identify factor and effect that influence modal shift occur from public transport to the alternative transport which is e-Hailing system. Johor Bahru area was the selected area as the location of the study due popular with the e-Hailing system. This study also shows the type of e-Hailing system that is used and will know the how this system really works with the safety, cost and also travel time. The binary logistic regression analysis shows that all the components were positively significant. This alternative transport is actually sending the user to the destinations that are selected by the user in the application. Therefore, the e-Hailing system is an alternative transport that must be used for people nowadays.